Social Comparison Information Influences Intentions to Reduce Single-Use Plastic Water Bottle Consumption - Bruchmann, Kathryn; Chue, Sarah M.; Dillon, Keelin; Lucas, Jaime K.; Neumann, Kayla; Parque, Charlotte (Frontiers in Psychology, 2021)
Single-use plastic consumption is at an all time high and threatens environmental and human health. College campuses in particular serve as a hub for single-use plastics due to their convenience for students on the go. The present research tests whether social comparison information can influence self-perceptions of single-use plastic consumption and motivate behavior change within the college campus environment. In a controlled experiment, we measured college students’ existing plastic water bottle usage and gave them false feedback about their behaviors and relative standing to their classmates: participants in comparison conditions learned they were either above or below average in their plastic water bottle sustainability behaviors. Results indicated that (relative to a no-comparison control), being above average at water bottle sustainability led students to be more satisfied with their sustainability efforts. However, either kind of comparison information (i.e., being above or below average) led to greater behavioral intentions to reduce single-use plastic water bottle consumption in the future. This study highlights how comparison information can be used to motivate sustainable behavior change with regards to single-use plastics.